THE INFLUENCE OF RETURN ON INVESTMENT (ROI), EARNING PER SHARE (EPS), AND SALES GROWTH ON STOCK PRICES OF METALS SUB SECTOR COMPANIES AND THE LIKE LISTED ON IDX FOR 2018-2020 PERIOD - Muhammad Rasyidi; Kasmadi Kasmadi; Rani Munika (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to analyze the effect of ReturnInvestment (ROI), Earning Per Share (EPS) and Sales Growth to Share Price. The population in this study are 17 metal and similar sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used is purposive sampling and obtained a sample of 13 companies. The data used is secondary data in the form of annual financial reports obtained from the Indonesia Stock Exchange website (www.idx.co.id) and the like. The analysis technique used in this research is multiple linear regression. The results showed that the independent variable ROI partially did not have a significant effect on stock prices, while the EPS and Sales Growth variables had a significant effect on stock prices. Simultaneously, ROI, EPS and Sales growth. The close relationship that occurs between the variables ROI, EPS and Sales Growth is categorized as strong with a correlation coefficient of 74.2% and the contribution of the independent variable to the dependent variable is 48.8% while 51.2% is influenced by other variables not included in this research model.